SPSS statistics for data analysis and visualization - McCormick, Keith (Consultant); Salcedo, Jesus (Consultant); Peck, Jon; Wheeler, Andrew (John Wiley & Sons, Inc., 2017)
This book includes the basics of SPSS Statistics to show you advanced techniques that exploit the full capabilities of SPSS. The authors explain when and why to use each technique, and then walk you through the execution with a pragmatic, nuts and bolts example. Coverage includes extensive, in-depth discussion of advanced statistical techniques, data visualization, predictive analytics, and SPSS programming, including automation and integration with other languages like R and Python.